2020
DOI: 10.1103/physrevb.101.155142
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization between the ligand p band and Fe3d orbitals in the p-type ferromagnetic semiconductor (Ga,Fe)Sb

Abstract: Ga,Fe)Sb is a promising ferromagnetic semiconductor for practical spintronic device applications because its Curie temperature (TC) is above room temperature. However, the origin of ferromagnetism with high TC remains to be elucidated. Here, we use soft x-ray angle-resolved photoemission spectroscopy (SX-ARPES) to investigate the valence-band (VB) structure of (Ga0.95,Fe0.05)Sb including the Fe-3d impurity band (IB), to unveil the mechanism of ferromagnetism in (Ga,Fe)Sb. We find that the VB dispersion in (Ga0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The direct comparison between the unfolded band structure of Ga 1−x Fe x Sb for x=0.125 calculated by hybrid functional HSE06 method and the band structure of pristine GaSb showed that, even though the heavily magnetic dopants, the properties of the host semiconductor were not strongly affected. It was also found that there is good agreement between the unfolded band structure of Ga 1−x Fe x Sb for x=0.125 and the experimental XAS and RPES spectra [26] of Ga 1−x Fe x Sb for x=0.137 concerning the energy position of the spectral weight of Fe-3d states. Moreover, the obtained results are in good agreement with the experimental finding for Ga 1−x Fe x Sb with x=0.137 that the Fe-3d electrons are correlated with itinerant character [17,20,27].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The direct comparison between the unfolded band structure of Ga 1−x Fe x Sb for x=0.125 calculated by hybrid functional HSE06 method and the band structure of pristine GaSb showed that, even though the heavily magnetic dopants, the properties of the host semiconductor were not strongly affected. It was also found that there is good agreement between the unfolded band structure of Ga 1−x Fe x Sb for x=0.125 and the experimental XAS and RPES spectra [26] of Ga 1−x Fe x Sb for x=0.137 concerning the energy position of the spectral weight of Fe-3d states. Moreover, the obtained results are in good agreement with the experimental finding for Ga 1−x Fe x Sb with x=0.137 that the Fe-3d electrons are correlated with itinerant character [17,20,27].…”
Section: Introductionsupporting
confidence: 53%
“…As a result of the application of HSE06 functional, the introduction of the non-local exchange effect corrects the bang gap value. By soft x-ray (SX) ARPES, T. Takeda et al have determined the band dispersion of GaSb along the Γ − K − X line [26]. In this experiment, the binding energy values of the peak positions of energy distribution curves (EDCs) for GaSb are located at −4 eV and −7 eV.…”
Section: Host Semiconductor Gasbmentioning
confidence: 99%
“…The band structures of (In,Fe)As and (Ga,Fe)Sb were observed by angle-resolved photoemission spectroscopy (ARPES), and it was found that Fe-induced IB is close to or overlapped with the CB bottom and VB top, respectively. 110,112) Because the band edge is resonant with the energy of the Fe-induced IB (E C ≈ ε d or E V ≈ ε d ), N 0 α and N o β are large according to Eq. ( 1).…”
Section: Efficient Magnetization Switching By Sotmentioning
confidence: 99%
“…In the field of spintronics, dilute magnetic semiconductors (DMSs) that simultaneously provide intrinsic ferromagnetism and semiconducting properties can be achieved by substituting cations in conventional semiconductors with transition metals (TMs) or rare-earth elements, which have attracted much attention in recent decades. [1][2][3][4][5] Among these semiconductors, the III-V GaSb-based DMSs have attracted a large amount of research interest because of their possible high T C values and intrinsic ferromagnetism, [6][7][8][9][10][11][12][13][14][15] which are critical in applications. Sato et al theoretically predicted that the T C of Mn-doped GaSb would be proportional to the Mn concentration.…”
Section: Introductionmentioning
confidence: 99%